1996
DOI: 10.1086/117918
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Barred Galaxies in the Virgo Cluster

Abstract: A study of the distribution of barred and nonbarred disk galaxies in the Virgo cluster is presented in an attempt to use the frequency and spatial distribution of galaxies with specific morphological features to study the efficiency of various environmental effects on the evolution of disk galaxies in clusters. The velocity distribution of the barred spirals in the Virgo region is clearly different than that of the nonbarred spirals, suggesting that barred spirals are more common in the main condensation of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 25 publications
6
28
0
Order By: Relevance
“…The pioneering work of Thompson (1981) showed an increased fraction of barred galaxies in the central region of the Coma cluster indicating that tidal interactions trigger bar formation. Similar results were also found in other samples, especially for early-type galaxies (see Giuricin et al 1993;Andersen 1996;Eskridge et al 2000;Barazza et al 2009;Lansbury et al 2014;Lin et al 2014). More recently, Méndez-Abreu et al (2012) showed that the effect of the environment on the bar formation depends on the mass of the galaxy.…”
Section: Introductionsupporting
confidence: 88%
“…The pioneering work of Thompson (1981) showed an increased fraction of barred galaxies in the central region of the Coma cluster indicating that tidal interactions trigger bar formation. Similar results were also found in other samples, especially for early-type galaxies (see Giuricin et al 1993;Andersen 1996;Eskridge et al 2000;Barazza et al 2009;Lansbury et al 2014;Lin et al 2014). More recently, Méndez-Abreu et al (2012) showed that the effect of the environment on the bar formation depends on the mass of the galaxy.…”
Section: Introductionsupporting
confidence: 88%
“…A similar result was reported by Varela et al (2004). Interestingly, while the fraction of barred disks in clusters or groups is not higher than in the field (Kumai et al 1986;van den Bergh 2002van den Bergh , 2007Marinova et al 2009), Thompson (1981) and Andersen (1996) presented evidence that barred galaxies in the Coma and Virgo clusters are more concentrated toward the cluster centers than unbarred disks.…”
Section: Introductionsupporting
confidence: 72%
“…An analysis of the clustercentric distances of barred galaxies in the Coma cluster (Thompson 1981) showed that a significantly larger fraction of barred galaxies are located at the cluster core than larger clustercentric distances (the adopted core radius for Coma was ∼784 kpc). In a similar study of the Virgo cluster, Andersen (1996) found that the barred disk galaxies are more centrally concentrated than the unbarred disks. For S0 galaxies, the same study found that the distributions of barred and unbarred objects are the same.…”
Section: The Distribution Of Barred Galaxies Within the Clustersmentioning
confidence: 91%
“…Thompson (1981) found a larger fraction of barred galaxies in the core of the Coma cluster and Giuricin et al (1993) reported a higher recurrence of early-type barred spirals in high local density environments. Later studies of local (Andersen 1996;Eskridge et al 2000) and intermediate-redshift clusters (Barazza et al 2009) showed similar findings and, more recently, Méndez-Abreu et al (2012) proved that by taking into account the different luminosity ranges, it is possible to detect different effects of the environment for luminous and faint galaxies located in clusters or in the field. They propose that interactions in bright disk galaxies that are stable enough against interactions trigger bar formation, while for faint galaxies, interactions are strong enough to heat the disk, inhibiting bar formation.…”
Section: Introductionmentioning
confidence: 69%